Fritschiella aquatilis (Chaetophoraceae, Chlorophyta), a new freshwater green algae species from China - Su, Hang; Feng, Jia; Lv, Jun-Ping; Liu, Qi; Nan, Fang-Ru; Xie, Shu-Lian (Phytotaxa, 2019)
A new freshwater algal species of Fritschiella aquatilis was found in a freshwater aquarium in China (Shanxi Province), floating on the surface or sinking at the bottom of the water. This new species is characterized by bright-green, globular thallus with hairy morphology, which composed numerous small single celled filamentous branches. Most characteristics are in agreement with description of Fritschiella. But the new species differs from other members in this genus by the particularly aquatic habitat and macroscopic thalli morphology (the only reported Fritschiella tuberosa Iyengar species is terrestrial). Concatenated sequences from 28S rDNA, 18S rDNA, rbcL gene phylogenetic analysis of F. aquatilis to discuss taxonomic status. All phylogenetic trees have yielded a Fritschiella clade included the sequence, and F. aquatilis formed an independent branch evidently distinguished from other species. Comparing with F. tuberosa, the internal transcribed spacer (ITS) secondary structure of the new species has some compensatory base changes (CBCs) and hemi-CBCs, especially at the Helix1 and Helix 2 end. Thus, the results of morphological and molecular characteristics support F. aquatilis to be recognized as a new species. This new alga brings the total number of recognized Fritschiella species, and the habitats circumscription of the genus Fritschiella expanded to include terrestrial and aquatic.